2004
DOI: 10.1017/s0952836904005618
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reproductive effort in male ungulates

Abstract: In ungulates, males and females have contrasting life histories, as usually only the females raise the young. How reproductive effort in males varies with individual level and population level characteristics has received little attention in the literature. Using published information on direct (weight loss during the rut) and indirect (rutrelated changes in activity budgets, fighting frequency, etc.) measures of reproductive effort, we tested whether effort in males increased with (H 1 ) increasing age, (H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 79 publications
3
99
2
Order By: Relevance
“…Higher somatic growth before prime age is expected to detract from reproductive resources (Yoccoz et al 2002, Mysterud et al 2004, Garel et al 2006. In our study, the growth rates of both body weight and antler size were higher after mixed age class harvest, but contrary to our predictions, on the coast also the maturation size (when reaching prime age) was higher (Fig.…”
Section: Discussioncontrasting
confidence: 86%
“…Higher somatic growth before prime age is expected to detract from reproductive resources (Yoccoz et al 2002, Mysterud et al 2004, Garel et al 2006. In our study, the growth rates of both body weight and antler size were higher after mixed age class harvest, but contrary to our predictions, on the coast also the maturation size (when reaching prime age) was higher (Fig.…”
Section: Discussioncontrasting
confidence: 86%
“…Activity was higher for old than young dominant males during the early-and peak-rut weeks. Past studies found activity during the mating season to be generally higher for old than for young males (Skogland 1989, Kojola 1991, Mysterud et al 2004. During the late-rut week we found that old males reduced their activity level.…”
Section: Discussionsupporting
confidence: 45%
“…For capital breeding mammals, the amount of weight lost over the mating season is considered a direct indicator of male reproductive effort (Yoccoz et al 2002, Mysterud et al 2005, Galimberti et al 2007. Behavioural indices, such as performance of agonistic behaviours or activity budgets during the mating season, are also often used in studies as indirect measures of male reproductive effort (see references in Mysterud et al 2004). Few studies have looked into the relationship between these two measures.…”
Section: Introductionmentioning
confidence: 99%
“…In several ungulate species, males experience serious weight loss during the rut, which is considered a direct measure of RE (Lott 1979;Mysterud et al 2004). Indirect measures of RE are rut-related changes in activity budgets, fighting frequency and tending of females (Mysterud et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In several ungulate species, males experience serious weight loss during the rut, which is considered a direct measure of RE (Lott 1979;Mysterud et al 2004). Indirect measures of RE are rut-related changes in activity budgets, fighting frequency and tending of females (Mysterud et al 2004). Males face a trade-off between investment in current reproduction or in other fitness components such as survival (Mainguy and Côté 2008) and need to balance their activity budgets between investing in RE (access to females, competition to males, patrolling territory) and investing in maintenance activity such as feeding and resting (Willisch and Ingold 2007).…”
Section: Introductionmentioning
confidence: 99%